برنامج مقترح من منظور الممارسة العامة في الخدمة الاجتماعية للتغلب على عنف الأزواج تجاه زوجاتهم - أسليم، إبراهيم عبدالمعطي (جامعة بغداد - كلية التربية للبنات, 2022)
تعد قضية عنف الأزواج تجاه زوجاتهم من القضايا ذات الأهمية البالغة في العلوم الاجتماعية، لذا تتجه الدراسة الحالية إلى محاولة تحديد مستويات العنف الذي يمارسه الأزواج ضد زوجاتهم، وذلك من أجل الوصول إلى برنامج مهني من منظور الممارسة العامة للخدمة الاجتماعية للتغلب على عنف الأزواج الذي يمارسونه ضد زوجاتهم، وتعد الدراسة من الدراسات الوصفية؛ إذ استعمل الباحث منهج المسح الاجتماعي الشامل، ولتحقيق هدف الدراسة أعد الباحث استبانة تكونت من جزأين، الأول: يضم البيانات الأولية للمبحوثين، والثاني: يضم (38) عبارة موزعة على أربعة محاور لقياس مستويات العنف وأنواعه لدى أفراد العينة، وطبقت الدراسة في بيت الأمان لرعاية النساء المعنفات في غزة، وبلغت عينة الدراسة (26) امرأة معنفة. أشارت نتائج الدراسة إلى أن مستوى العنف النفسي هو الأكثر انتشاراً فقد بلغت نسبته (81.3%) ثم العنف الجسدي بنسبة (68.6%) ثم العنف الاجتماعي بنسبة (68%)، وأخيراً العنف الاقتصادي بنسبة (66.6%) كما وأشارت النتائج بعدم وجود فروق ذات دلالة إحصائية بين مستوى العنف الذي يمارسه الأزواج ضد زوجاتهم في بيت الأمان لرعاية النساء المعنفات تبعاً لمتغير (الحالة التعليمية للزوجة، عدد الأبناء)، وفي ضوء النتائج توصلت الدراسة إلى برنامج مقترح من منظور الممارسة العامة للتغلب على عنف الأزواج الذي يمارسونه ضد زوجاتهم. Husbands’ violence towards their wives is one of the greatly important issues in social sciences. Accordingly, the current study aims at determining the levels of violence practiced by husbands towards their wives to propose a professional program from the perspective of the general practice of social work to overcome such a phenomenon. The study is descriptive in nature, where the researcher has used a comprehensive social survey method. To achieve the goal of the study, the researcher has prepared a questionnaire that consisted of two parts. The first part contains the primary data of the two sections, and the second contains (38) phrases distributed over four axes to measure the levels and types of violence among the sample’s members. The study has been conducted in the Safety House to Care for Abused Women in Gaza. The study’s sample amounted to (26) battered women. The results have revealed that the level of psychological violence is the most prevalent (81.3%), then comes physical violence (68.6%), then social (68%), and finally, comes economic violence (66.6%). The Study concluded that there are statistically significant differences between the level of violence practiced by husbands towards their wives in the Safety House for the care of battered women according to the variables of wife's educational status, and number of children. In light of these results, the study has concluded a proposed program from the perspective of general public practice to overcome husbands' violence against their wives
Keywords: العنف المجتمعي -- العلاقات الزوجية -- النساء المعنفات -- العنف الأسري